Relativistic option pricing - Vítor Hugo Ferreira Carvalho; Raquel M. Gaspar (International Journal of Financial Studies, 2021)
The change of information near light speed, advances in high-speed trading, spatial arbitrage strategies and foreseen space exploration, suggest the need to consider the effects of the theory of relativity in finance models. Time and space, under certain circumstances, are not dissociated and can no longer be interpreted as Euclidean. This paper provides an overview of the research made in this field while formally defining the key notions of spacetime, proper time and an understanding of how time dilation impacts financial models. We illustrate how special relativity modifies option pricing and hedging, under the Black-Scholes model, when market participants are in two different reference frames. In particular, we look into maturity and volatility relativistic effects.
Keywords: G100; G120; G170; G190; 330; econophysics; proper time; spacetime finance; time dilation